Development of Digital Modules on Particle Motion Dynamics Material using Augmented Reality Media Assisted MOOCs to Improve Learning Outcomes of Grade XI High School Students - Triani, Deswinta; Risdianto, Eko; Medriati, Rosane (Universitas Syiah Kuala, 2025)
The research was used to describe the feasibility of digital modules using augmented reality media assisted by MOOCs, describe student responses and describe the improvement of student learning outcomes after the implementation of digital modules using augmented reality media assisted by MOOCs. This type of research is research and development (RD) with the ADDIE development model. The subjects in this study consisted of 36 students in class XI.2 of SMA Negeri 8 Bengkulu City. The results of the study show that the feasibility test criteria for digital modules using augmented reality media assisted by MOOCs are at 92.5% with the category of very feasible. The response given by students to the use of the developed digital module was at 87% with the very good category. From the pretest and posttest sheets using Gain scores, the results were obtained that students experienced an increase in learning outcomes after using the digital modules that had been developed. It can be concluded that digital modules using augmented reality media assisted by MOOCs are very feasible to be used as learning alternatives and can improve student learning outcomes, especially in physics subject matter, namely particle motion dynamics.